Kajian Manajemen Biaya Pendidikan dalam Meningkatkan Kualitas Layanan Pada Perguruan Tinggi Bidang Maritim - Teguh Purnomo; Nafi Almuzani; Darul Prayogo; Abdi Seno (Universitas Pendidikan Indonesia, 2021)
The purpose of the research is review the cost of education on the ability to pay and assessment of student satisfaction in uni-versities, especially in the maritime field. Research is outlined in the description taken data from several information retrieval techniques, further literature studies are used as support for nar-rative development. The results illustrate students provide a good assessment of the cost of education and the quality of services held but the concept of budgeting mechanisms is still not affordable information by students. To improve the quality of service quality, in accordance with applicable regulations and policies, in the implementation of monitoring and evaluation of service quality, agencies/educational institutions are required to take customer satisfaction assessment. In the development of realizing a quality education, of course the implementation will not be separated from the financing element. In universities, the cost of education is still a major issue in the implementation of education. The benefits of the research are expected to contribute informa-tion to the mechanism of cost budgeting and improve-ment of education services as well as provide an understanding of the importance of balance of education costs, quality of education services and become a reference for further research from observations.